Ulceronecrotic penicillosis - Romita Bachaspatimayum; Thangjamang Haokip; G Zamzachin; Yanglem Elizabeth Devi (Wolters Kluwer Medknow Publications, 2015)
A 40-year-old male human immunodeficiency virus (HIV) -positive patient on highly active antiretroviral therapy (HAART) developed bilateral cervical lymphadenopathy with fine needle aspiration cytology (FNAC) showing yeast cells of Penicillium marneffei. The adenopathy disappeared after 9 months of itraconazole therapy at a dose of 200 mg/day. Seven years later and 2 days following second-line HAART, the patient presented with generalized papulonodules and ulceronecrotic lesions. Biopsy of the skin lesion revealed plenty of yeast forms dividing by binary fission morphologically resembling Penicillium marneffei. Significant improvement was observed at 2 weeks of starting itraconazole 400 mg/day. After 3 months, the dose was reduced to 200 mg/day and advised to continue for 6 months. Penicillosis presenting initially in the form of cervical adenopathy and later, developing typical skin lesions rapidly progressing to ulcerative and necrotic erosions may be due to continued immunosuppression followed by immune reconstitution inflammatory syndrome (IRIS).